Budget optional procedures in the light of Constitution of Poland and selected constitutional regulations of Europeans countries - Łukasz Kielin (Prawo Budżetowe Państwa i Samorządu)
The author raises the problem of optional procedures which are applied when a state budget act is not adopted. The article discusses the problem of the constitutional relations between the state budget and provisional budget as well as other optional procedures. Author compares the debt rule which is derived from the Constitution of the Republic of Poland with other similar regulations in other selected European legal orders. The article ends with a summary which contains postulates de lege ferenda.